2012
DOI: 10.12717/dr.2012.16.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent Index of Mitotic Interval (τ0) for Chromosome Manipulation in Korean Bullhead, Pseudobagrus fulvidraco

Abstract: Korean bullhead (Pseudobagrus fulvidraco) was collected from the Kum River areas of Kangkyung-eup, Nonsan city, Chungcheongnam-do, Korea, from April to June, 2012 and was fertilized in order to observe egg development and temperature-related cleavage rates and mitotic intervals (τ0). The fertilized eggs were separative, demersal and light yellowish with 1.5±0.06 mm in diameter, and did not contain oil globules. The first cleavage stages were 90 min, 80 min, 60 min and 50 min at 21°C , 24°C , 27°C and 30°C , re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Approximately 10% of fertilized eggs reached first cleavage frequency every 15 min. These results are similar to those reported by Ignat’eva (1975) , Saat & Veersalu (1996) , Park & Im (2001) , and Kim et al (2011) showing that faster development has occurred at higher water temperature.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Approximately 10% of fertilized eggs reached first cleavage frequency every 15 min. These results are similar to those reported by Ignat’eva (1975) , Saat & Veersalu (1996) , Park & Im (2001) , and Kim et al (2011) showing that faster development has occurred at higher water temperature.…”
Section: Resultssupporting
confidence: 92%
“…3 , we found that grass puffer showed faster development with decreased mitotic intervals when water temperature was increased, indicating a strong negative correlation between τ 0 and water temperature. Besides this study, similar results on the reduction of mitotic interval according to rising water temperature have been reported in far eastern catfish ( Silurus asotus ) , black plaice ( Pleuronectes obscurus ), and Korean rose bitterling, Rhodeus uyekii ( Park & Im, 2001 ; Park and Im, 2010 ; Kim et al, 2011 ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation